A novel polymer-based nitrocellulose platform for implementing a multiplexed microfluidic paper-based enzyme-linked immunosorbent assay - Lin, Dong; Li, Bowei; Fu, Longwen; Qi, Ji; Xia, Chunlei; Zhang, Yi; Chen, Jiadong; Choo, Jaebum; Chen, Lingxin (Microsystems & nanoengineering, 2022)
Nitrocellulose (NC) membranes, as porous paper-like substrates with high protein-binding capabilities, are very popular in the field of point-of-care immunoassays. However, generating robust hydrophobic structures in NC membranes to fabricate microfluidic paper-based analytical devices (μPADs) remains a great challenge. At present, the main method relies on an expensive wax printer. In addition, NC membranes very easy to adhere during the printing process due to electrostatic adsorption. Herein, we developed a facile, fast and low-cost strategy to fabricate μPADs in NC membranes by screen-printing polyurethane acrylate (PUA) as a barrier material for defining flow channels and reaction zones. Moreover, hydrophobic barriers based on UV-curable PUA can resist various surfactant solutions and organic solvents that are generally used in immunoassays and biochemical reactions. To validate the feasibility of this PUA-based NC membrane for immunoassays in point-of-care testing (POCT), we further designed and assembled a rotational paper-based analytical device for implementing a multiplexed enzyme-linked immunosorbent assay (ELISA) in a simple manner. Using the proposed device under the optimal conditions, alpha fetoprotein (AFP) and carcinoembryonic antigen (CEA) could be identified, with limits of detection of 136 pg/mL and 174 pg/mL, respectively, which are below the threshold values of these two cancer biomarkers for clinical diagnosis. We believe that this reliable device provides a promising platform for the diagnosis of disease based on ELISA or other related bioassays in limited settings or remote regions.